The Effect of Bedroom Wall Colors on Users' Perceptual Performance - Yıldırım, Kemal; Müezzinoğlu, Menşure Kübra; Şahin, Seda; İnan, Beray (Selcuk University, 2024)
In this study, the effects of colour types (neutral, warm, cool) selected based on single-colour harmony used on the walls of bedrooms, where individuals spend a significant part of their lives, on participants’ perceptual evaluations were examined. Within the scope of the study, virtual bedroom spaces designed according to different colour types were used to investigate how perceptual evaluations of research participants could be influenced. The study formulated hypotheses based on the relationships between bedroom colour type and participant variables such as occupation, gender, and age. To test these hypotheses, participants evaluated virtual bedroom spaces online using Google Forms. Statistical analyses, including confidence tests conducted with SPSS, involved calculating percentage values, means, and standard deviations. Differences among variables were examined comparatively. The findings indicated that spaces utilizing neutral colours were generally perceived more positively compared to those employing warm and cool colours. Moreover, certain groups, namely engineers and other professionals, men, and participants aged 25-35, tended to provide more favourable perceptual evaluations than architects, interior designers, women, and participants aged 36-50. In conclusion, this study contributes to understanding how colour types in bedroom environments can influence perceptual evaluations, shedding light on preferences across various demographic groups.

Bu araştırmada, bireylerin yaşamlarının önemli bir bölümünü geçirdikleri yatak odalarının duvarlarında kullanılan tek renk harmonisine dayalı olarak seçilen renk türlerinin (nötr, sıcak, soğuk) katılımcıların algısal değerlendirmeleri üzerindeki etkileri incelenmiştir. Çalışma kapsamında, farklı renk türlerine göre tasarlanan sanal yatak odası mekanları ile, araştırma katılımcılarına ait algısal değerlendirmelerin ne şekilde etkilenebileceği araştırılmıştır. Araştırmanın hipotezleri ile, yatak odalarında kullanılan renk türü ile meslek, cinsiyet ve yaş gibi değişkenler arasındaki ilişkilere dayanarak oluşturulmuştur. Araştırma hipotezlerini test etmek için, katılımcılardan sanal yatak odası mekanlarını çevrimiçi olarak değerlendirmeleri istenmiştir, bu değerlendirme Google Formlar aracılığıyla gerçekleştirilmiştir. Toplanan veriler SPSS programı kullanılarak güven testlerine tabi tutulmuş, yüzdelik dilimler, ortalamalar ve standart sapma gibi istatistiksel değerler hesaplanarak, değişkenlerin arasında tespit edilen farklılıklar karşılaştırmalı şekilde incelenmiştir. Bu çalışma sonucunda, nötr renklerin tercih edildiği mekanların genel olarak sıcak ve soğuk renklerin tercih edildiği mekanlara göre daha olumlu bir şekilde algılandığı saptanmıştır. Ayrıca, mühendislerin ve diğer meslek gruplarının, erkeklerin ve 25-35 yaş aralığındaki katılımcıların, mimarlar ve iç mimarlar, kadınlar ve 36-50 yaş grubundaki katılımcıların, daha olumlu değerlendirmelerde bulunduğu tespit edilmiştir.
Yatak Odası Duvar Renklerinin Kullanıcıların Algısal Değerlendirmeleri Üzerindeki Etkisi
Keywords: Interior Architecture; İç Mimarlık